HYDROCARBON POTENTIAL OF THE SOUTH-EASTERN UNDERTHRUST PART OF PRECARPATHIAN’S FOREDEEP OUTER ZONE - Михайлів, Ірина Романівна; Мазур, Анна Павлівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
One of the most perspective for oil and gas expected areas in Western Ukraine is Mesozoic part of Pokutsko – Bukovyna Carpathians underthrust. During last years here was made a lot of seismological research and exploration drilling. Basing on them were built structure maps of Cretaceous sediments. And actually basing on those structure maps we can get the conclusion for perspective structures inside the area and give possible reasons of oil and gas deposits absence.